Influencing Motivational Factors on Consumer Buying Behaviour of Luxury Goods: A Self-Determination Theory Perspective - Zenginer, Melis (2016)
Since the luxury market has experienced a great growth in the last two decades, luxury consumer research is still a field, which does not have enough research. Researchers in this field point out that luxury goods are a great way to show consumer’s status and wealth, but it includes rarely the aspirations and intrinsic ones. In order to address this research gap this dissertation aims to identify consumers’ motivations for purchasing luxury goods. Building on Self-Determination Theory, it is investigated whether consumers’ intrinsic values lead “self-directed luxury purchase” in which consumers make a conscious choice of purchasing luxury for its timeless style over short-lived fashion and long-lasting quality over excessive quantity. Additionally, it is discussed whether extrinsic values drive a traditional, “conspicuous luxury purchase”. It is measured to find out whether self-directed or conspicuous luxury purchase leads repurchase intention. Data were collected from 205 consumers and analysed using multiple regression analysis. 205 responses revealed the critical roles that intrinsic values and extrinsic values played in luxury consumption, respectively. It is also vital to mention that self-directed luxury purchase predicted positive affect more strongly than did conspicuous luxury purchase stressing the significance of self-directed luxury purchase in creating positive emotional responses toward luxury brands, which ultimately lead to repurchase intention.